PRELIMINARY RESULTS OF FIRST PILOT PROJECT TO ASSESS THE BIOLOGICAL ADAPTABILITY AND ZOOTECHNICAL PERFORMANCE OF THE DUSKY GROUPER (Epinephelus marginatus) IN NORTHEASTERN BRAZIL: Resultados preliminares do primeiro projeto piloto para avaliar a adaptabilidade biológica e o desempenho zootécnico da garoupa- verdadeira (Epinephelus marginatus) no nordeste do Brasil - Lisboa, Viviana; Tavares Torres, Marcelo; da Costa Albuquerque Filho, Antônio; Lacerda Teixeira de Souza, Marcelo; Silva, Ana Cláudia; Lopes, Pedro; Nogueira Matias, João Felipe (Arquivos de Ciências do Mar, 2024)
This note records the preliminary results obtained during the course of the first pilot project to investigate the adaptability and zootechnical performance of dusky grouper Epinephelus marginatus in northeastern Brazil. The project started with first juvenile transport from Prime Seafood Marine Farm, Alcobaça – BA - Brazil, to Mirante Pescados, Cascavel – CE – Brazil, and is running with individuals maintained in a float net cage, enclosed in a frame tank padded with plastic liner, with a land-based Recirculating Aquaculture System (RAS). The biological adaptation was evaluated by fish survival and feed intake. Growth performance by zootechnical indexes was estimated through biometric measurements. During this initial report period (14th November 2021 to 9th February 2022) fish were hand-fed twice daily (8:00 a.m. and 5:00 p.m.) at a rate of 1.5 % total biomass. The water quality parameters were monitored regularly, at least once a week, and commercial probiotic was added to the water tank. Water quality remained in the range tolerable for the species and to February 2022, survival is 100%. The feeding behavior has been immediate consumption of all offered food, demonstrating the biological adaptability of the dusk grouper. Over the 87-days report period, the juveniles showed a significant (P < 0.05) improvement in growth performance and reached an average weight and length of 290.2 ± 4.7 g and 25.03 ± 0.1 cm. Likewise, the mean apparent food ration converse and specific growth rate were 1.33 and 0.77 (% -day). The preliminary pilot project has already accomplished the first successful transport of groupers to Ceará – Brazil; attest the ability of the dusky grouper E. marginatus to be adapted to a new hot and dry environment and the preliminary growth performance indicates there is great potential of dusky grouper production in northeastern Brazil. Keywords: Mariculture, marine finfish, fish farming.